Illness does not know about holidays. Experience of a hospitaly stay - Candela Bonill de las Nieves; César Hueso Montoso (Universidad de Alicante, 2012)
A biographical report provides a greater approach to personal experiences and in particular to the health-disease process. The fact of being admitted to a hospital causes the person to face situations of uncertainty, lack of control, threatening feelings, etc, situations that become even worse if the stay turns out to be unpleasant because of the institution organizational problems. We present Pilar's report, a woman who describes her experience during her stay in a hospital during a holiday period. The problems she had on admission such as the closing of some wards, the lack of information, the staff work overload, the insecurity and the lack of privacy, are the main dimensions that emerge from the speech of the informant.